Gas-liquid equilibrium prediction of system CO 2 -aqueous ethanol at moderate pressure and different temperatures using PR-EOS - Arkan Jasim, Hadi; J., Hadi Ghassan; Najmuldeen, Ghazi Faisal; Iqbal, Ahmed; Syed F., Hasany (National Library of Serbia, 2013)
One of the most important design considerations which should not be ignored during the equipment designing for some industrial purpose is vapour-liquid equilibrium (VLE). Thus, in chemical engineering, the first step is the computation of VLE properties of materials by employing Equation of state (EOS). In this study, we have used a thermodynamic model which was established for binary system of carbon dioxide (1)-(2) solubility of CO2 in aqueous ethanol and it was employed to estimate the gas-liquid equilibrium at moderate pressures (till 6 bar) and varying temperatures (288 K to 323 K). Peng-Robinson EOS was employed to determine the VLE properties. Mixing rules such as vanderWaals and quadratic mixing rules were also used for the determination of ethanol-water mixture critical parameters which entails the pseudo-critical method as one component and results obtained from this study were similar to the ones reported in recent literature for empirical phase equilibrium studies.